A new logical insight and putative mechanism behind fluoxetine-induced amenorrhea, hyperprolactinemia and galactorrhea in a case series. (December 2013) - Mondal, Somnath; Saha, Indranil; Das, Saibal; Ganguly, Abhrajit; Das, Debasis; Tripathi, Santanu Kumar
With the exception of fluoxetine, all selective serotonin reuptake inhibitors (SSRIs) commonly cause hyperprolactinemia through presynaptic mechanisms indirectly via 5-hydroxytryptamine (5-HT)-mediated inhibition of tuberoinfundibular dopaminergic neurons. However, there is little insight regarding the mechanisms by which fluoxetine causes hyperprolactinemia via the postsynaptic pathway. In this text, analysis of five spontaneously reported clinical cases of hyperprolactinemia resulting in overt symptoms of amenorrhea with or without galactorrhea, were scrupulously analyzed after meticulously correlating relevant literature and an attempt was made to explore the putative postsynaptic pathway of fluoxetine inducing hyperprolactinemia. Hypothetically, serotonin regulates prolactin release either by increasing oxytocin (OT) level via direct stimulation of vasoactitive intestinal protein (VIP) or indirectly through stimulation of GABAergic neurons. The pharmacodynamic exception and pharmacokinetic aspect of fluoxetine are highlighted to address the regulation of prolactin release via serotonergic pathway, either directly through stimulation of prolactin releasing factors (PRFs) VIP and OT via 5-HT2A receptors predominantly on PVN (neurosecretory magnocellular cell) or through induction of 5-HT1A -mediated direct and indirect GABAergic actions. Prospective molecular and pharmacogenetic studies are warranted to visualize how fluoxetine regulate neuroendocrine system and cause adverse consequences, which in turn may explore new ways of approach of drug development by targeting the respective metabolic pathways to mitigate these adverse impacts.